Celestial mechanics, spacecrafts, and 50th years of the first humans on the Moon - Gomes, Vivian Martins [UNESP] (2018)
Aerospace engineering is a relatively new topic in engineering. It deals with several aspects of activities related to space. It includes Astrodynamics, which is a field that studies the motion of spacecraft, like guidance and control, which studies different forms to guide the motion of a spacecraft, etc. All those fields started from the Celestial Mechanics, one of the first topics studied in Astronomy. The first studies had the goal to record and explain the motions of the stars, with special attention given to the motion of some irregular stars, which showed later to be planets. Considering the advances in the technology, those earlier studies generated the space activities that are well known nowadays. Different topics, like orbital and attitude maneuvers and determination of spacecrafts, mission design, etc. are covered. The present Focus Issue publishes several papers related to aerospace engineering in general and can be useful for further studies and planning of space missions.